Abnormal octadeca-carbon fatty acids distribution in erythrocyte membrane phospholipids of patients with gastrointestinal tumor. Issue 24 (June 2017) - Lin, Shaohui; Li, Tianyu; Liu, Xifang; Wei, Shihu; Liu, Zequn; Hu, Shimin; Liu, Yali; Tan, Hongzhuan
Abstract : Abstract: Fatty acid (FA) composition is closely associated with tumorigenesis and neoplasm metastasis. This study was designed to investigate the differences of phospholipid FA (PLFA) composition in erythrocyte and platelet cell membranes in both gastrointestinal (GI) tumor patients and healthy controls. In this prospective study, 50 GI tumor patients and 33 healthy volunteers were recruited between the years 2013 and 2015. Blood samples were collected from healthy volunteers and patients, and FA composition was assessed using gas chromatography-mass spectrometer (GC-MS), and data were analyzed by multifactor regression analysis. Compared with healthy controls, the percentages of C18:0 (stearic acid, SA), C22:6 (docosahexaenoic acid, DHA), and n-3 polyunsaturated FAs (n-3 PUFA) were significantly increased, while C18:1 (oleic acid, OA), C18:2 (linoleic acid, LA), and monounsaturated FAs (MUFA) decreased in erythrocyte membranes of GI tumor patients. Also, patient's platelets revealed higher levels of C20:4 (arachidonic acid, AA) and DHA, and lower levels of OA and MUFA. Our study displayed a remarkable change in the FA composition of erythrocyte and platelet membranes in GI tumor patients as compared with healthy controls. The octadeca-carbon FAs (SA, OA, and LA) in erythrocyte membranes could serve as a potential indicator for GI tumor detection. Abstract : Supplemental Digital Content is available in the text